Decision Support System for Recruitment of Employees in CV. Fajar Jaya Using TOPSIS Method - Abdul Aziz; Ari Waluyo; Friska Elena Wardani (Politeknik Piksi Ganesha Indonesia, 2023)
Employees are one of the main needs of the company because if there are no employees, there will be no productivity in the company. Recruitment is a human resource management planning decision regarding the number of employees needed, when they are needed, and what criteria are needed. CV Fajar Jaya has a problem in making employee recruitment decisions. Decision making is very important for individuals and organizations. The difficulty of recruiting qualified employees is the main problem in this study, with the above problems, it is necessary to design a decision support system that is expected to help CV. Fajar Jaya, in making decisions to obtain information to determine prospective employees using the TOPSIS method, which is expected to use the topsis calculation method, the final results of the selection process for new employee candidates are more effective, selective, efficient and accurate at CV. Fajar Jaya